Amyotrophic Lateral Sclerosis Symptom Score in Integrative Treatments (ALS-SSIT) for Evaluating Therapeutic Effect of Traditional Chinese Medicine: A Prospective Study. (16th April 2022) - Zheng, Xuanlu; Schröder, Joana; Sima, Dandan; Wang, Mingzhe; Wang, Qiudong; Pan, Weidong
Abstract : Objective . To evaluate the reliability, validity, sensitivity, and clinical applicability of a new scale—the amyotrophic lateral sclerosis symptom score in integrative treatments (ALS-SSIT)—for measuring the effect of traditional Chinese medicine (TCM) in patients with amyotrophic lateral sclerosis (ALS). Methods . A total of 160 patients with ALS were enrolled and followed up for 6 months. All patients received TCM. Patients were evaluated at enrollment and at the end of 6 months with a new scale, the ALS-SSIT, developed after extensive consultations with TCM experts with several years of experience in the treatment of ALS. The 36-item Medical Outcomes Study Short Form (SF-36) scale and the amyotrophic lateral sclerosis functional rating scale (ALSFRS) were used as the reference standards. Results . The acceptance rate and completion rate of the ALS-SSIT scale were high, and the content validity was confirmed by experts. Test-retest performed at enrollment and at 6 months showed good reliability of the ALS-SSIT scale (Cronbach α, 0.9172 and 0.9181, respectively). The ALS-SSIT scale score showed significant change at 6 months, indicating the ability to reflect the change in disease severity. Conclusion . The ALS-SSIT appears to be a feasible, reliable, and sensitive tool for the evaluation of the effect of TCM in patients with ALS.